Meningkatkatkan Hasil Belajar Matematika Melalui Model Problem Based Learning - Soleman Talib; La Yusran La Kalamu (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the increase in student learning outcomes in class VIII on Number Patterns through the Problem Based Learning Model. This type of research is a Classroom Action Research (PTK). The subjects in this study were students of class VIII SMP Negeri 12 Kota Tidore Kepulauan. The research was conducted in 1-2 cycles. Data retrieval in this study was carried out using the Learning Outcomes test and observation sheet on the teacher's ability to manage learning based on the Problem Based Learning Model and observing student activity in Problem Based Learning based learning. Based on the results of field data analysis, it is necessary to improve the quality of learning by offering various one of the methods used, namely the Problem Based Learning Learning Model is very effective in learning mathematics, especially learning materials that involve students directly in solving a problem